Effectiveness of Structured Counseling Program for Patients with Newly Diagnosed Essential Hypertension - Shrestha, Anmol Purna; Shrestha, Abha; Shrestha, Roshana; Karmacharya, Robin Man; Thakur, Chanda; Shrestha, Rashmi; Vaidya, Nirish; Karmacharya, Biraj Man (Journal of Nepal Health Research Council, 2025)
Background: The burden of hypertension is high in our context. Poor adherence contributes to poor hypertension control. This pilot study aims to study the effect of structured counseling programs on antihypertensive therapy adherence and blood pressure control.Methods: This is an effectiveness-implementation hybrid design type I- Quasi-experimental feasibility study. We recruited newly diagnosed hypertensive patients under antihypertensives with 50 each in the intervention and control group. We adapted existing guidelines to devise a structured counseling program. The intervention group underwent the counseling program. We called both groups after one month to assess the adherence and blood pressure control.Results: We recruited 100 newly diagnosed hypertensive patients. Twenty-two participants dropped out in the one-month follow-up visit. Among the remaining 78 individuals, 73 (94%) demonstrated good adherence. The post-intervention median (IQR) of medication adherence scores assessed with the Medication Adherence and Report Scale (MARS) in the intervention and control groups after one month was 50 (48-50) and 48 (43.5-50) respectively (p=0.015). The immediate knowledge score increased significantly in the intervention group after the structured counseling. Nevertheless, there was no significant change in systolic and diastolic pressure recordings in the intervention group one-month post-intervention when compared to that of the control group.Conclusions: The findings of this pilot study suggest that the structured counseling program should be tailored to local needs and should be compounded with regular follow-ups for reinforcement, drug reminders, and family and peer support along with a collaborative effort to ensure adherence and control.Keywords: Adherence; antihypertensive; hypertension management; structured counseling.